Ewolucja polityki Wspólnoty wobec krajów Afryki, Karaibów i Pacyfiku - Jantoń-Drozdowska, Elżbieta (The Evolution of the European Community's Policy Towards Africa, Caribbean and Pacific Countries, 2009)
The aim of this study is to present the policy of the European Community (EU) towards Africa, Caribbean and Pacific countries (ACP) and the economic relationships between them. The author will also tend to assess how effective a support of the EU is for promoting the economic development of this group of countries. The European Community policy towards the ACP countries has changed after the expiration of the Lomé IV Convention. The Cotonou Agreement, signed in June 2000, has created a new arrangement for economic relations between the two partners. At present the trade preferences are reciprocal (earlier the EU offered the associated countries non-reciprocal trade preferences) and the financial and technical aid is higher but more conditioned than in the past. The ACP countries worry that new trade provisions may worsen their future economic situation and competitiveness in the world market.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 593-605